PENGUATAN DASA WISMA DALAM PEMBERDAYAAN KADER KESEHATAN PADA PENYAKIT HIPERTENSI UPAYA PENCEGAHAN GAGAL JANTUNG DI SIDOARJO - Moch Bahrudin; Tanty Wulan Dari; Siti Maimuna; Titik Sumiatin; Su'udi; Wahyu Tri Ningsih (Jurnal Abdi Masyarakat, 2026)
Health cadres are one of the pillars of Family Empowerment and Welfare, serving as a link between health workers and the community. Therefore, one of their responsibilities is to ensure that community members are in good health, particularly in managing hypertension, where there are still differing perspectives among the community in addressing hypertension as part of efforts to prevent heart failure, and these differences require intervention. In this situation, health cadres play a crucial role in managing hypertension and preventing it from worsening. This initiative aims to empower health cadres through capacity-building programs focused on appropriate hypertension management in Jambangan Village. The author used several methods to carry out the empowerment, such as lectures, discussions, question-and-answer sessions, and fun games. As a result of this activity, most participants were able to understand the definition, criteria, symptoms, and mild treatment of hypertension. There were three questions from the participants: physical activity management, first aid for hypertension, and how to take hypertension medication.